2021
DOI: 10.1186/s12348-021-00242-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course, treatment and visual outcome of an outbreak of Burkholderia contaminans endophthalmitis following cataract surgery

Abstract: Background Postoperative endophthalmitis is a rare but dreaded complication of intraocular surgery and often results in severe visual impairment or blindness. The present study describes the clinical course, treatment and visual outcome of an outbreak of Burkholderia contaminans endophthalmitis following cataract surgery. Methods Among 290 patients who underwent uneventful phacoemulsification cataract surgery at one outpatient clinic between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 30 publications
2
30
1
Order By: Relevance
“…Outcomes of the Narvik patients were compared to literature Bcc POE reports. describes the treatment of all patients at UNN, and we agree with that table except for the exact dates of POE diagnoses and their omission of the second eye of case 3 [8].…”
Section: Methodssupporting
confidence: 77%
See 4 more Smart Citations
“…Outcomes of the Narvik patients were compared to literature Bcc POE reports. describes the treatment of all patients at UNN, and we agree with that table except for the exact dates of POE diagnoses and their omission of the second eye of case 3 [8].…”
Section: Methodssupporting
confidence: 77%
“…Previous studies have found Bcc to have low susceptibility to the commonly used IC antibiotics, including cefuroxime (administered here -ESCRS protocol) and vancomycin, but is usually sensitive to ciprofloxacin [20,22,24,29]. Culture results in this series showed resistance to cefuroxime, with sensitivity to ceftazidime, ciprofloxacin, gentamicin and piperacillin/tazobactam, the last of which is generally effective against Bcc [8]. All patients recovered final corrected distance visual acuity of 20/25 or better, likely because Lind., et al performed a "persistent and intensive treatment approach" with IOL explantation and total lens capsule removal (for all except both eyes of case 3) [8].…”
Section: Betweenmentioning
confidence: 63%
See 3 more Smart Citations